Kepercayaan Diri dengan Minat Berwirausaha pada Generasi Z di Kelurahan Kadipaten Kota Yogyakarta - Meylita Ayu Herbafalony; Theresia Dewi Setyorini; Femmy Lekahena (Jurnal Psikologi, 2025)
Entrepreneurial interest in Generation Z plays an important role in efforts to reduce unemployment rates and drive economic growth through the creation of self-employment opportunities. This study aims to empirically prove the relationship between self-confidence and entrepreneurial interest among Generation Z in Kadipaten Village, Yogyakarta City. The sample in this study consisted of 136 Generation Z individuals, selected using probability sampling with stratified cluster random sampling techniques, from a total population of 272 Generation Z individuals. Data was collected using the Entrepreneurial Interest Scale and the Self-Confidence Scale. The data analysis technique used was Pearson Product Moment correlation analysis. The results of the study show a positive and significant relationship between self-confidence and entrepreneurial interest among Generation Z in Kadipaten Village, Yogyakarta City, with a correlation coefficient of 0,482 (p<0,01).